2017
DOI: 10.1002/ange.201705122
|View full text |Cite
|
Sign up to set email alerts
|

Silver‐Catalyzed Stereoselective Aminosulfonylation of Alkynes

Abstract: As ilver-catalyzed intermolecular aminosulfonylation of terminal alkynes with sodium sulfinates and TMSN 3 is reported. This three-component reaction proceeds through sequential hydroazidation of the terminal alkyne and addition of as ulfonyl radical to the resultant vinyl azide.T he method enables the stereoselective synthesis of aw ide range of bsulfonyl enamines without electron-withdrawing groups on the nitrogen atom. These enamines are found to be suitable for av ariety of further transformations.Alkynes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 63 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…We observed that no product formation was occurring in the presence of eosin Y after 12 hours (table 1 entry We were astonished to see that only I2 (Iodine) could bring the desired conversion (Table 1, entry 10), and other catalytic conditions provided the desired product with low reaction yield or no reaction ( Table 1, entries 1-6). Encouraged by these findings, our studies were directed to look at the prospective different molar ratio of iodine and Cs2Co3 (cesium carbonate) with ethanol as a solvent ( Table 1, entry [11][12][13][14], but none of these could match the efficacy of model condition which provided thiosulfonate product 3(a-r) in good yield at room temperature in the presence of blue led light (Table 1, entry 10). To screen the effect of time, the model reaction was undertaken under the prevailing conditions in pressure tube using I2 as a catalyst at varying time duration.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that no product formation was occurring in the presence of eosin Y after 12 hours (table 1 entry We were astonished to see that only I2 (Iodine) could bring the desired conversion (Table 1, entry 10), and other catalytic conditions provided the desired product with low reaction yield or no reaction ( Table 1, entries 1-6). Encouraged by these findings, our studies were directed to look at the prospective different molar ratio of iodine and Cs2Co3 (cesium carbonate) with ethanol as a solvent ( Table 1, entry [11][12][13][14], but none of these could match the efficacy of model condition which provided thiosulfonate product 3(a-r) in good yield at room temperature in the presence of blue led light (Table 1, entry 10). To screen the effect of time, the model reaction was undertaken under the prevailing conditions in pressure tube using I2 as a catalyst at varying time duration.…”
Section: Resultsmentioning
confidence: 99%
“…[12]. Recently, the cross-coupling reaction of sulfonyl hydrazides with thiols (or sodium sulfinates with disulfides) has been developed for the preparation of thiosulfonates with the help of transitional metal catalysts [13], Sodium sulfinates [14] and sulfoxides [15] are also important organosulfur compounds. Alternatively, thiosulfonates can be obtained by thiosulfonate exchange reactions of sulfenamides, by the reaction of potassium thiosulfonates with diaryliodonium salts [16].…”
Section: Introductionmentioning
confidence: 99%
“…Many methodologies and sulfur sources have been developed to install a variety of sulfur functionalities into organic molecules [11][12][13][14] . Among these, the use of sulfur-centered radicals to access sulfur-containing compounds has attracted considerable attention due to their ease of generation and e ciency of reaction [15][16][17][18][19][20] . However, in contrast to the popularity of sulfonyl and thiyl radicals, the utilization of sul nyl radicals in synthetic chemistry has remained unexplored.…”
Section: Main Textmentioning
confidence: 99%
“…A single report suggested that their thermal decomposition might proceed via homolytic ssion, generating two distinct sulfur-centered radicals-a sul nyl radical and a sulfonyl radical 34 . As sulfonyl radicals are known to undergo facile addition to π-bonds [17][18][19] , sul nyl sulfones appeared to be well suited for our envisioned strategy. Here we describe the successful generation and use of sul nyl sulfones in radical addition / radical coupling reactions with a wide variety of unsaturated hydrocarbons (Fig.…”
Section: Main Textmentioning
confidence: 99%
“…Recently, our group described a copper-catalyzed four-component reaction of terminal alkynes, aryldiazonium tetrafluoroborates, DABCO·(SO 2 ) 2 , and potassium halide, giving rising to a range of β-halo alkenylsulfones ( Xiang et al., 2017 ). Inspired by this work and recent advances in the reactions of alkynes with trimethylsilyl azide via a radical process ( Liu et al., 2019b ; Wang et al., 2015 ; Wu et al., 2019 ; Xiong et al., 2019 ; Ning et al., 2017 ), we conceived that the sulfone-containing alkenyl azide intermediates might be accessed through the azidosulfonylation of alkynes with the insertion of sulfur dioxide via a radical process. Driven by the importance of tetrazole chemistry and our continuous interest in the insertion of sulfur dioxide, we envisioned that the incorporation of sulfonyl unit into tetrazoles for the construction of valuable sulfonylated tetrazoles might be beneficial for various biological evaluations.…”
Section: Introductionmentioning
confidence: 99%